IMPROVING STUDENTS ABILITY IN WRITING TEXT OF SPEECH USING CRITICAL WRITING METHOD (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2018)
This research is motivated by the problem of writing the text of speech in SDN Adiyasa, Rancaekek, Bandung District. Based on the results of field observations found many students who are less able to write text speech, still difficult to pour ideas in making text speech. and ignore the spelling in writing. The problem arises not only caused by students, but also because of less effective, creative, and fun teaching lessons. The purpose of this research is to improve the process and ability of students in writing text of speech. The research method used is class action research method by using Elliot Design. This study was conducted with three cycles that each cycle consisted of three actions. In this study, researchers used instruments such as observation sheets, field notes, documentation and interviews. Data analysis was done by quantitative, qualitative and triangulation technique. Quantitative data is done by searching for average, while qualitative data is processed by descriptive method. Judging from the ability to write speech texts, each cycle has increased. This is evident from the average score of speech-writing ability obtained by students from each cycle. Cycle I: 55.23 Cycle II: 66.11 and Cycle III: 87.98 and thus the researchers recommend to teachers to use the Critical Writing Multiliteration method as one of the solutions to improve speech writing skills.